Immigrants' Language Skills and Visa Category - Barry R. Chiswick; Yew Liang Lee; Paul W. Miller (Institute for the Study of Labor (IZA), 2002)
This paper is concerned with the determinants of English language proficiency among immigrants in a longitudinal survey for Australia. It focuses on both visa category and variables derived from an economic model of the determinants of destination language proficiency among immigrants. Skills tested and economic immigrants have the greatest proficiency shortly after immigration, followed by family-based visa recipients, with refugees having the lowest proficiency. These differences disappear by 3 – years after immigration for speaking skills, but they persist for reading and writing skills. The variables generated from the model of destination language proficiency are in part predictions of visa category and are more important statistically for explaining proficiency. The effects of some variables on language skills increase with duration in these longitudinal data. In particular, the efficiency variable, age, and gender, which may be reflecting differences in labor market attachment, increase in importance over time.
Keywords: J24; J61; J18; 330; immigration; language proficiency; visa categories; Australia; Migranten; Sprache; Einwanderungsrecht; Schätzung; Australien